PKM Pengembangan Koperasi Desa Bonto Mangngiring Kecamatan Bulukumpa Kabupaten Bulukumba - Ackhriansyah Ahmad Gani; Andi Muhammad Ikhsan; Mahathir Mohammad (Universitas 17 Agustus 1945 Semarang, 2023)
Community Service Activities (PkM) is one part of the Tri Dharma of Higher Education which must be carried out by the academic community, especially teaching staff. Service with the title PKM DEVELOPMENT OF BONTOTIRO VILLAGE COOPERATIVE BULUKUMBA DISTRICT.PKM activities are carried out to increase participants' skills, abilities and knowledge in solving problems that occur in their environment. This community service aims to provide understanding to the community, especially the Islamic boarding school environment, regarding how to develop a cooperative as a basis for increasing the use of cooperatives as business entities as well as as a people's economic movement that is tough, strong, independent and superior as an economic actor that mobilizes the economic capabilities of the people in the area. national economy.